2015
DOI: 10.1016/j.dadm.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of amyloid‐positron emission tomography neuroimaging: Practical and bioethical considerations

Abstract: Until recently, estimation of β-amyloid plaque density as a key element for identifying Alzheimer's disease (AD) pathology as the cause of cognitive impairment was only possible at autopsy. Now with amyloid-positron emission tomography (amyloid-PET) neuroimaging, this AD hallmark can be detected antemortem. Practitioners and patients need to better understand potential diagnostic benefits and limitations of amyloid-PET and the complex practical, ethical, and social implications surrounding this new technology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…In the AD patients, senile plaques were detected in the hippocampus (Sabri et al, 2015; Witte et al, 2015). Accumulating evidences have shown that 9-month-old APP/PS1 transgenic mice exhibited the formation of senile plaques which gradually increased with age (Bibari et al, 2013; He et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the AD patients, senile plaques were detected in the hippocampus (Sabri et al, 2015; Witte et al, 2015). Accumulating evidences have shown that 9-month-old APP/PS1 transgenic mice exhibited the formation of senile plaques which gradually increased with age (Bibari et al, 2013; He et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid imaging increases the level of information available to clinicians and may also aid in prognostication [31]. Few data are available to guide the clinical interaction around amyloid imaging, however, beyond the proposed appropriate use criteria [11, 32] and initial recommendations for communicating scan results [33, 34](Grill et al, submitted ). To examine how amyloid imaging affects the diagnostic experience for patients and families, we performed a telephone interview study with patients and caregivers who received clinical care at an academic tertiary memory disorders clinic.…”
Section: Introductionmentioning
confidence: 99%
“…It will also be necessary to investigate the impact of special education for clinicians who handle amyloid imaging information, an important topic as recently pointed out by different groups (50)(51)(52). This education should contain lines of arguments on why there is clinical utility to both PET imaging outcome scenarios (amyloid positivity and negativity).…”
Section: Future Perspectivesmentioning
confidence: 99%